Analisis Pengaruh Lokasi dan Kualitas Pelayanan terhadap Peningkatan Penjualan Kewirausahaan UMKM Kuliner (Studi Kasus pada “Ayam Geprek Mas Boy” Di Bandar Lampung) - Daud, Syahril; Putri, Afrenea Miranda; Fitri, Elysa Amisa; Anlisyah, Inariva Misel (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze the influence of location and service quality on increasing sales at Ayam Geprek Mas Boy. In the fast food culinary industry, strategic location and high quality service are crucial factors that can increase customer satisfaction and frequency of visits. The methodology used is a quantitative approach by collecting data from respondents through a Likert scale questionnaire. The analysis results show that strategic business locations contribute to increasing the number of customers, while service quality proves significant in increasing customer satisfaction and loyalty. The regression test shows that service quality has a greater influence than location on increasing sales. This research contributes to culinary entrepreneurs in understanding the importance of these two variables to achieve success in a competitive market.